2022
DOI: 10.5339/qmj.2022.29
|View full text |Cite
|
Sign up to set email alerts
|

Seropositive Neuromyelitis Optica in a Case of Undiagnosed Ankylosing Spondylitis: A Neuro-Rheumatological Conundrum

Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune astrocytopathy against foot processes of aquaporin-4 (AQP4) water channels. Patients with NMOSD tend to have other coexisting autoimmune/connective tissue diseases. However, AQP-4-antibody-positive NMOSD coexisting with ankylosing spondylitis (AS) is rare. AS is an immune-mediated disorder, a subset of axial spondyloarthropathies, which commonly manifests as chronic inflammatory back pain in young people, and it has a strong association with HLA-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Patient with NMOSD tends to have other coexisting autoimmune/connective tissue diseases. However, AQP‐4‐antibody‐positive NMOSD coexisting with ankylosing spondylitis (AS) is rare 11 . AS and NMOSD share an obscure pathogenesis, while a T‐cell‐based autoimmunity is a possible explanation for the disease process considering the recently role of T cell in NMOSD and molecular mimicry might be an environmental factor that results in co‐pathogenesis 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient with NMOSD tends to have other coexisting autoimmune/connective tissue diseases. However, AQP‐4‐antibody‐positive NMOSD coexisting with ankylosing spondylitis (AS) is rare 11 . AS and NMOSD share an obscure pathogenesis, while a T‐cell‐based autoimmunity is a possible explanation for the disease process considering the recently role of T cell in NMOSD and molecular mimicry might be an environmental factor that results in co‐pathogenesis 12 .…”
Section: Discussionmentioning
confidence: 99%
“…11 AS and NMOSD share an obscure pathogenesis, while a T-cell-based autoimmunity is a possible explanation for the disease process considering the recently role of T cell in NMOSD and molecular mimicry might be an environmental factor that results in co-pathogenesis. 12 Ritwik Ghosh et al 11 reported a 35-year-old Indian man with an undiagnosed progressive axial spondyloarthropathy (i.e., AS) is reported presenting with acute-onset LETM, a clinical subset of NMOSD. Lin et al describe the case of a 46-year-old Chinese female with bilateral lower limbs and perineum numbness.…”
Section: Discussionmentioning
confidence: 99%